EVALUATION OF HAEMOGLOBINOPATHIES IN BALANGIR DISTRICT OF WESTERN ODISHA- A HOSPITAL BASED STUDY FROM A TERTIARY HEALTH CARE CENTER (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Hemoglobinopathies are genetic disorders related to Haemoglobin. Haemoglobinopathies in Odisha is a significant public health concern, particularly among tribal population. Western region of Odisha has a good tribal population and significant studies regarding the prevalence and burden of haemoglobinopathy in this area is sparse. Objective: To Determine different spectrums of abnormal haemoglobin, in the patients attending Pathology department, sent from various clinical department of Bhima Bhoi Medical College and Hospital. Material and Methods: This observational study was carried out in the Department of Pathology of Bhima Bhoi Medical College and Hospital, Balangir, Odisha, from August 30, 2024 to 31th May 2026. 2ml of EDTA blood sent by other department for evaluation of haemoglobinopathy. CBC, sickling  test slide, peripheral blood smear were performed for every case and Haemoglobin patterns were analyzed by Chromatogram Interpretation Ready Reckoner, ß Thalassemia Mode, HLC-723G8 (TOSOH INDIA PVT. LTD). Result: A total of 1678 patients were studied, out of which 723 patients were detected with abnormal Haemoglobin. Sickle cell trait was found to be most common, followed by was Sickle cell homozygous cases. Conclusion: The higher prevalence of haemoglobinopathy in our study is attributed to the advanced diagnostic tools and selective sampling of clinically doubtful cases sent to our department for study. Public awareness, Proper Anti-natal care and genetic counselling will definitely help community in decreasing the disease burden.